Protein Expression Landscape Defines the Formation Potential of Mouse Blastoids From EPSCs - Min, Zheying; Zhong, Ke; Luo, Yuxin; Fan, Yong; Yu, Yang (Frontiers in Cell and Developmental Biology, 2022)
Preimplantation embryo development is a precisely regulated process organized by maternally inherited and newly synthesized proteins. Recently, some studies have reported that blastocyst-like structures, named blastoids, can be generated from mouse ESCs (embryonic stem cells) or EPSCs (extended pluripotent stem cells). In this study, to explore the dynamic expression characteristics of proteins and their PTMs in mouse EPS blastoids, we revealed the protein expression profile of EPS blastoids and metabolite characteristics by TMT-based quantitative mass spectrometry (MS) strategy. Furthermore, the protein phosphorylation sites were identified to show the phosphoproteomic analysis in blastoids compared with mouse early embryos. Above all, our study revealed the protein expression profile of EPS blastoids compared with mouse embryos during preimplantation development and indicated that glucose metabolism is key to blastoid formation.